Research on The Ultra-Low Emission Technology in Internal Combustion Engine - Azhar, Muhammad Izzudin; Mohd Fazri, Azrul Fadzli; Khalid, Amir; Azizul, Muhamad Asri; Zainal Abidin, Shaiful Fadzil; Ismail, Muammar Mukhsin; Darlis, Nofrizalidris (Journal of Automotive Powertrain and Transportation Technology, 2023)
Increasing the efficiency of internal combustion engines is a technologically proven and cost effective approach to dramatically improving the fuel economy of the nation’s fleet of vehicles in the near- to midterm, with the corresponding benefits of reducing our dependence on foreign oil and reducing carbon emissions. This review paper discusses on the research of ultra-low emission technology in internal combustion engine. Efficiency can be increased by improving combustion processes, minimizing engine losses such as friction, reducing the energy penalty of the emission control system and using recovered waste energy in propulsion. Compliance with exhaust emission regulations will be mandated and requires after-treatment technologies integrated with the engine combustion approaches. Fuels under consideration include hydrocarbon-based. Because of their relatively low cost, high performance, and ability to utilize renewable fuels, internal combustion engines, including those in hybrid vehicles, will continue to be critical to our transportation infrastructure for decades.